2022
DOI: 10.1007/s10833-022-09458-2
|View full text |Cite
|
Sign up to set email alerts
|

Innovating teaching and instruction in turbulent times: The dynamics of principals’ exploration and exploitation activities

Abstract: In turbulent environments, schools have to adapt to constantly changing conditions. According to ambidexterity theory, whether they are successful in this primarily depends on their leaders and how they manage the tension between the use of current knowledge (exploitation) and the search for new knowledge (exploration). Through unique top-down and bottom-up pathways, they thus influence the innovation outcome of a school. However, it is so far unclear whether these assumptions are correct. Using data from a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 107 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Similarly, Yap et al [ 43 ] reported improved organisational performance as a result of management's ambidexterity. Pietsch et al [ 44 ] observed that school leaders' exploitation and exploration activities contributed to better innovative performance. Finally, Luu et al [ 45 ] found that public employees' ambidexterity supports customer value co-creation.…”
Section: Performance Impacts Of Eamentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Yap et al [ 43 ] reported improved organisational performance as a result of management's ambidexterity. Pietsch et al [ 44 ] observed that school leaders' exploitation and exploration activities contributed to better innovative performance. Finally, Luu et al [ 45 ] found that public employees' ambidexterity supports customer value co-creation.…”
Section: Performance Impacts Of Eamentioning
confidence: 99%
“…Yap et al [ 43 ] found that perceived environmental dynamism is strongly and positively associated with employees' ambidexterity. Congruent with these arguments, Mom et al [ 35 ] and Pietsch et al [ 44 ] posited that highly uncertain work contexts enhance employees' ambidextrous behaviours. Moreover, organisations benefit from ambidextrous behaviours in dynamic work environments rather than in constant and specific work contexts [ 35 ].…”
Section: Drivers and Constraints Of Eamentioning
confidence: 99%
“…However, the investigation of the impact of an innovative climate in schools has become especially important in the wake of the COVID-19 pandemic. With the rapid spread of COVID-19, teachers in schools are required to develop new teaching skills and facilitate meaningful learning experiences (Pietsch et al, 2023;R€ ohl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted during the COVID-19 crisis have highlighted the pivotal role of principals in driving innovation amidst uncertainty (Da'as et al, 2022;Pietsch et al, 2023). Schools that successfully combined the preservation and utilization of existing capabilities while exploring new ones were able to foster innovation (Beauchamp et al, 2021;Harris and Jones, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation